Relationship between nutrition literacy and dietary adherence among hemodialysis patients from selected dialysis centers in the Klang Valley, Malaysia - Lim, Jun Hao (2021)
Limited health literacy and dietary non-adherence are significant public health issues in the hemodialysis (HD) population, especially in low-and-middle-income countries, where health resources and dietitians are limited. Nutrition literacy is a specific type of health literacy concerning eating practices. It has recently been recognised as a plausible predictor of dietary adherence in HD patients. Yet, information pertaining to nutrition literacy and dietary adherence among Malaysian HD patients is scant. Importantly, theoretical frameworks have posited the putative mechanisms that explain the relationship continuum from health literacy and its determinants to dietary adherence through patient’s related factors (i.e., knowledge, health belief, and self-management skills). Nevertheless, empirical study to address such a mechanism is scarce. Thus, this study aimed to explore an existing health literacy skills framework to (1) determine the prevalence rates of limited nutrition literacy and dietary non-adherence, (2) identify the determinants of nutrition literacy, (3) examine the relationship between nutrition literacy and dietary adherence, and (4) investigate the mediation effects of patient-related factors on the relationship between nutrition literacy and dietary adherence among Malaysian HD patients. A multi-centre, cross-sectional study was conducted at nine convenient and accessible dialysis centres in Klang Valley, Malaysia. A total of 250 multi-ethnic Malaysian HD patients who aged ≥ 18 years, dialysed thrice-weekly ≥ six months, absence of physical impairment, cognitive problem, terminal illness, and other conditions that might bias the study outcome, were randomly selected. Data collection was conducted via face-to-face interview using pretested and validated semi-structured questionnaire. Dietary adherence was measured using the End-Stage Renal Disease Adherence Questionnaire (ESRD-AQ) and serum potassium and phosphate levels. At the same time, self-management skills were assessed by the Perceived Kidney/Dialysis Self-Management Scale (PKDSMS). While self-developed and validated scales were used to gauge nutrition literacy (i.e., Dialysis Specific Nutrition Literacy Scale, DSNLS), dietary knowledge (i.e., Dialysis Diet Knowledge Questionnaire, DDKQ) and five health belief model (HBM) constructs (i.e., Dialysis Diet-Related Health Belief Questionnaire, DDHBQ), including perceived benefits, perceived barrier, perceived seriousness, perceived susceptibility, and perceived self-efficacy. Data analyses were performed using IBM SPSS version 25 and Smart PLS version 3. Null hypotheses were tested based on the results of multiple linear regression and partial least squares structural equation modeling. A total number of 218 HD patients were recruited. They consisted of 53.2% male and had a mean age of 54.8 ± 12.8 years. The ethnicity distribution was 56.4% Malay, 29.8% Chinese, and 12.8% Indians, resembling the Malaysian HD population. The majority of the study respondents have completed secondary education (46.3%). The mean dialysis vintage was 67.2 ± 54.3 months. Most of them had rarely received dietary advice from healthcare professional (44.5%), high level of dietary knowledge (52.3%), high perceived benefit (72.5%), moderately high perceived barrier (38.1%), high perceived seriousness (74.3%), moderately low perceived susceptibility (35.3%), and moderately low perceived self-efficacy (42.0%) of dietary adherence as well as moderately high selfmanagement skills (55.5%). Limited nutrition literacy was evident in 46.3% of HD patients. Older age (β=-0.212, p=0.017), lower education level [no formal education (β=-0.143, p=0.039), primary education (β=-0.462, p<0.001), and secondary education (β=-0.277, p=0.001), as compared to tertiary education], shorter dialysis vintage (β=0.159, p=0.016), and have never received dietary advice from healthcare professional [as compared to “every 2-3 months” (β=0.160, p=0.040) and “when blood tests showed abnormal results” (β=0.160, p=0.040)], were the determinants of nutrition literacy. Overall the multiple regression model explained 34.4% of variance of the nutrition literacy. The prevalence of dietary nonadherence was estimated at 65.1% based on patients’ self-report. Age (β=0.185, p=0.024), gender (βfemale=0.227, p=0.001), and nutrition literacy (β=0.372, p<0.001) were independent predictors of dietary adherence. Nutrition literacy appeared as a stronger predictor than sociodemographic factors, explaining about 10% variance of the selfreported dietary adherence. The relationship between nutrition literacy and dietary adherence was mediated comparably by self-efficacy (SIE=0.186, BC 95% CI 0.110 - 0.280) and self-management skills (SIE=0.192, BC 95% CI 0.103 - 0.304). Conversely, dietary knowledge, perceived benefits, barrier, seriousness and susceptibility could not explain the relationship between nutrition literacy and dietary adherence. In conclusion, limited nutrition literacy and dietary non-adherence are prevalent in Malaysian HD patients. Patients with older age, lower education level, shorter dialysis vintage and have never received dietary advice from healthcare professionals are at risk of limited nutrition literacy. Nutrition literacy is an independent predictor of dietary adherence in Malaysian HD patients. It is causally linked to dietary adherence through self-efficacy and self-management skills. Therefore, nutrition literacy-enhancing interventions targeting on self-efficacy and self-management skills should be considered in promoting dietary adherence among Malaysian HD patients.